ECOLOGICAL AND ECONOMIC EFFICIENCY OF FUNCTIONING OF AGRICULTURAL ENTERPRISES: THEORETICAL AND METHODOLOGICAL ASPECT - OKHOTA, Yuliia; NEDOBEIKO, Serhii (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article studies one of the most pressing problems of modern agricultural production – ensuring environmental and economic efficiency of the functioning of agricultural enterprises. In the context of increasing anthropogenic load on natural resources, climate change, intensification of production and increasing requirements for the economic performance of agricultural entities, achieving a balance between economic and environmental priorities appears as a key task for the sustainable development of the agricultural sector. Attention is focused on the versatility of the concept of environmental and economic efficiency, which covers both the achievement of high production and financial results and the minimization of negative impact on the environment. The paper presents an overview of scientific approaches to assessing environmental and economic efficiency, highlights the achievements of leading domestic and foreign scientists in this area. Particular attention is paid to the methodological foundations of the formation of integral indicators, which allow to comprehensively take into account the economic and environmental indicators of enterprises. A systematic approach to the analysis of efficiency, which takes into account the relationships between the components of the agroecosystem and external conditions of management, is proposed. The main groups of factors that affect the level of environmental and economic efficiency are characterized, among which technological innovations, climate change, environmental pollution, state policy and social factors are distinguished. In particular, the importance of introducing resource-saving technologies, increasing energy efficiency, supporting biodiversity and developing organic production was emphasized. The role of state regulation, environmental taxation, eco-incentives and support for «green» initiatives in increasing the efficiency of agricultural production at the national level was also noted. The results of the study allow us to conclude that there is a need to revise traditional management models in the agricultural sector in favor of an integrated environmental and economic approach. The practical significance of the article lies in the possibility of using the proposed methodology for assessing efficiency in the formation of strategies for the development of agricultural enterprises, the development of regional agroecological programs and the system of agrarian environmental monitoring. The work is a significant contribution to the development of scientific and methodological foundations of sustainable management in the agricultural sector of Ukraine.
Keywords: environmental and economic efficiency; agricultural enterprise; sustainable development; economic efficiency; environmental efficiency; agricultural sector